Creating Santripreneurs: Empowerment of Jepara Santri in Entrepreneurship with 3D-Based Furniture Design Training - Abdullah, Shodiq; Ratnawati, Zulfa; Hadi, Nor (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2022)
As technology developed, santri in Jepara started a furniture business with the skills gained when learning in Pesantren (Islamic boarding schools), studying (nyantrik) and training. This training aims to equip students with the skills to design 3D furniture to support their businesses. The training is carried out in two stages: 1) the preparation stage, selecting interested potential participants who have the motivation and potential to set up a furniture business; 2) the implementation stage with lecture, practice, question and answer methods and simulations. The results of the training show that; 1) Santri in Jepara is very interested in the furniture business, so they are excited and could learn 3D furniture design faster; 2) After attending the training, the students are able to: a) operate the SketchUp  program and can make simple furniture designs, b) develop furniture designs with various shapes, and some have tried to make carving designs, c) have a great enthusiasm to develop expertise in the furniture business by self-learning through social media.